CONCEPT OF FORM IN THE FILM DILAN 1990 - Rohma, Naafi Nur (Capture : Jurnal Seni Media Rekam, 2021)
The Dilan 1990 is an adaption film that chronicles the romance of high school teenagers in the 1990s. This film ranked first in terms of viewership in 2018. The allure of this film that warrants further analysis is its shape notion. This study aims to analyze the Dilan 1990 film's notion of form. This qualitative descriptive study analyzes data using the form concept methodology created by David Bordwell and Kristin Thompson. The findings indicate that the film's forms and processes are extremely complicated. The constructed elements are connected in such a way that they can excite the audience's emotions, most notably their expectations.